2011
DOI: 10.1371/journal.pone.0029537
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube Action between Human Mesothelial Cells Reveals Novel Aspects of Inflammatory Responses

Abstract: A well-known role of human peritoneal mesothelial cells (HPMCs), the resident cells of the peritoneal cavity, is the generation of an immune response during peritonitis by activation of T-cells via antigen presentation. Recent findings have shown that intercellular nanotubes (NTs) mediate functional connectivity between various cell types including immune cells - such as T-cells, natural killer (NK) cells or macrophages - by facilitating a spectrum of long range cell-cell interactions. Although of medical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…[2] Recent studies by other groups have confirmed the ability of an additional mTOR inhibitor (rapamycin) to decrease nanotube formation between benign mesothelial cells, as well as the association of cholesterol/lipid raft microdomains with TnTs. [9, 22, 23] Others have further demonstrated that depletion of cellular cholesterol using agents such as methyl-β-dextrin decreased the density of nanotubes between cells from a urothelial cancer cell line. [23] The same drug effectively reduced cholesterol concentrations and nanotube formation in human mesothelial cells cultivated in vitro .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2] Recent studies by other groups have confirmed the ability of an additional mTOR inhibitor (rapamycin) to decrease nanotube formation between benign mesothelial cells, as well as the association of cholesterol/lipid raft microdomains with TnTs. [9, 22, 23] Others have further demonstrated that depletion of cellular cholesterol using agents such as methyl-β-dextrin decreased the density of nanotubes between cells from a urothelial cancer cell line. [23] The same drug effectively reduced cholesterol concentrations and nanotube formation in human mesothelial cells cultivated in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…[23] The same drug effectively reduced cholesterol concentrations and nanotube formation in human mesothelial cells cultivated in vitro . [9] Paradoxically, the use of the HMG-CoA reductase inhibitor simvastatin - a drug in common medical use for treatment of hypercholesterolemia – led to significant increases in numbers of nanotubes. [9] Nonetheless, as the authors postulate, the distribution of cholesterol across individual cells may account at least in part for this finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[44][45][46] Moreover, some pathogens have been shown to exploit the related structures to spread among cells, [47][48][49][50] and TNFAIP2 mRNA expression appears to be upregulated under conditions known to enhance nanotube formation. 34,36,51,52 It is not yet clear whether the TNFAIP2-modulated actin protrusions in NPC cells are functionally related to the reported actin-based nanotubes; however, both the actin-based protrusive structures may share the same underlying mechanism that engages the actinremodeling proteins, such as Cdc42. In our previous study, we have revealed that LMP1 is able to activate Cdc42 by directly binding to FGD4, thereby promoting the migration of NPC cells.…”
Section: Discussionmentioning
confidence: 99%